EFEKTIVITAS PENGGUNAAN METODE TELENURSING TERHADAP KEPATUHAN PASIEN SKIZOFRENIA : A LITERATURE REVIEW - Batmanlussy, Viona Alfonsa; Sukihananto, Sukihananto (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Bengkulu, 2023)
Background : rapid advances in technology and information have also entered the world of nursing, especially psychiatric nursing. Telenursing is a method that is currently developing in psychiatric nursing because it can connect patients and nurses in an instant and only costs a little but has an effect on patient compliance. Objective : to describe the benefits of using the telenursing method in the world of nursing, especially psychiatric nursing. Methods : This study uses a literature review from several online databases such as Google Scholar, Scopus, Science Direct, and EBSCO using keywords in the form of telenursing, adherence, and schizophrenia. Results : from the literature review, it was found that telenursing is beneficial for patients, especially in medication adherence. In addition, telenursing is also beneficial for nurses, namely by helping nurses to observe patients being treated at home and helping patients to remain in stable condition. Conclusion : telenursing is beneficial for both the nurse and the patient. Keywords : adherence, schizophrenia, telenursing